Behavioral Finance Factors Influencing Investment Decisions: Financial Literacy, Attitude, Socialization, and Planning Behavior - jati handarukmi (Jurnal Ekonomika dan Bisnis, 2026)
The rapid development of digital investment platforms has increased public participation in various investment instruments. However, the growing number of investors has not always been followed by improvements in investment decision quality. Many investors, particularly beginners, still make decisions based on market trends, social recommendations, or limited financial analysis. This study aims to examine the influence of financial literacy, financial attitude, and financial socialization on investment decisions through financial planning behavior as a mediating variable. This study employs a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 210 respondents in Central Java Province who had investment experience. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4. The results indicate that financial planning behavior has a positive and significant effect on investment decisions. Financial literacy and financial attitude also positively influence investment decisions, while their effects on financial planning behavior are insignificant. Furthermore, financial socialization significantly influences financial planning behavior but does not directly affect investment decisions. These findings highlight that financial planning behavior serves as an important behavioral mechanism in transforming financial knowledge, attitudes, and social learning into investment decisions. This study contributes to behavioral finance literature by emphasizing that improving investment decision quality requires not only financial knowledge but also the development of consistent financial planning practices supported by social environments.